Severe Legionella pneumonia mimicking immune-related pneumonitis after chemoimmunotherapy for lung cancer: a case report - Liu, Haixian; Ding, Zhaolei; Xu, Lina; Guo, Tao (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have significantly improved survival outcomes and quality of life in patients with various malignancies. Nevertheless, their associated toxicities must not be overlooked. Although not the most common immune-related adverse event (irAE), CIP is recognized as one of the most serious. In particular, grade 3–4 CIP that is not promptly treated may compromise subsequent immunotherapy and can result in respiratory failure or even death. Legionnaires’ disease, caused by Legionella pneumophila, is an uncommon but potentially life-threatening form of atypical pneumonia. With the expanding use of ICIs, especially in combination with chemotherapy, early stage CIP and Legionella pneumonia may share similar radiological features, such as ground-glass opacities, which makes early differential diagnosis difficult. However, timely differentiation is critical because the management strategies differ substantially: CIP requires systemic corticosteroids, whereas Legionella pneumonia necessitates quinolone antibiotics. Traditional diagnostic methods for Legionella infection, including culture on specialized media and urine antigen testing, are limited by low sensitivity and the risk of false-negative results. In recent years, targeted next-generation sequencing (tNGS) has emerged as a valuable diagnostic tool. Compared with metagenomic next-generation sequencing (mNGS), tNGS offers a shorter turnaround time, higher sensitivity and specificity, and greater cost-effectiveness. As such, it is becoming increasingly important in the accurate identification of atypical pathogens in pulmonary infections.Case summaryWe report the case of a patient with squamous cell lung cancer who developed severe pneumonia following combined chemotherapy and immunotherapy. The initial working diagnosis was immune checkpoint inhibitor-related pneumonia (ICI-P) complicated by bacterial infection. However, sputum-targeted next-generation sequencing (tNGS) subsequently identified Legionella pneumophila infection. Following the administration of quinolone-sensitive antibiotics, the patient’s clinical condition improved markedly, and he was discharged in a stable state. A 70-year-old male farmer with a history of lung cancer, type 2 diabetes, and chronic obstructive pulmonary disease (COPD) was admitted on February 4, 2025,with fever, cough, and dyspnea following chemoimmunotherapy. He had received paclitaxel, cisplatin, and tislelizumab on January 24.Initial tests revealed leukopenia, neutropenia, and chemotherapy-induced myelosuppression. On admission, the patient exhibited hypoxemia, hyponatremia, and elevated inflammatory markers, raising suspicion for ICI-P complicated by bacterial infection. Despite empirical broad-spectrum antibiotics and corticosteroids, his condition deteriorated, requiring transfer to the Respiratory Intensive Care Unit (RICU). On February 13, tNGS of sputum identified Legionella pneumophila, Enterococcus faecium, Epstein-Barr virus (EBV),and Herpesvirus-1 (HSV-1). The high relative abundance of Legionella pneumophila indicated it was the primary pathogen; EBV and HSV-1 were presumed latent. Antimicrobial therapy was adjusted to moxifloxacin, cefepime, and ganciclovir, leading to clinical improvement and resolution of hypoxemia. Follow-up chest CT showed partial resolution of pulmonary infiltrates. The patient was discharged with home oxygen and outpatient follow-up.The patient is currently undergoing regular anti-tumor treatment.ConclusionsIn the era of chemoimmunotherapy, the presence of pulmonary ground-glass interstitial lesions should prompt consideration not only of immune checkpoint inhibitor-related pneumonia (ICI-P) but also of infections caused by uncommon pathogens such as Legionella, particularly when there is no significant improvement after corticosteroid therapy. It is necessary to consider applying advanced molecular diagnostic techniques such as targeted next-generation sequencing (tNGS) as early as possible to make a clear diagnosis of the pathogen and guide individualized treatment.